Students’ use of Internet-Based Payment Applications: An Extension of the Technology Acceptance Model Theory - Muchamad Syafruddin (Asian Journal of Applied Education (AJAE), 2026)
The main objective of this study is to identify and examine whether perceived organizational innovation (POI) moderates the relationship between perceived trust (PT), perceived risk (PR), social influence (SI), perceived ease of use (PEU), and perceived usefulness (PU) with the use of internet-based payment applications by students (IPA). The analysis is grounded in the Resource-Based Theory (RBT) as an extension of the Technology Acceptance Model (TAM). Data were collected using a survey method through questionnaires distributed to students who use internet-based payment systems. A total of 468 student respondents were obtained using a non-probability sampling method, specifically convenience (accidental) sampling. SPSS 25 was used to conduct descriptive statistical analysis and regression testing for all hypotheses. The results indicate that four factors—PT, SI, PEU, and PU—have a significant positive effect on the use of internet-based payment systems, while PR has a significant negative effect. Another finding shows that perceived organizational innovation (POI) significantly strengthens the relationship between all independent variables (PT, PR, SI, PEU, and PU) and the dependent variable (IPA).